Intersurgeon Cost Variability in Anterior Cervical Discectomy and Fusion. Issue 16 (August 2018) - Sielatycki, J. Alex; Chotai, Silky; Wick, Joseph; Sivaganesan, Ahilan; Devin, Clinton J.
Abstract : Study Design: Retrospective review of prospective patient outcomes and cost data. Objective: To analyze the contribution of surgeon-specific variability in cost and patient-reported outcomes (PROs) to overall variability in anterior cervical discectomy and fusion (ACDF), whereas adjusting for patient comorbidities. Summary of Background Data: Cost reduction in surgical care has received increased attention. Patient factors contributing to cost variability in ACDF have been described; however, intersurgeon cost and outcome variability has received less attention in the literature. Methods: Adult patients undergoing elective primary ACDF by five different surgeons were analyzed from a prospective registry database. Direct and indirect 90-day costs were compared across each surgeon, along with PROs. Predicted costs were calculated based on patient co-morbidities, and an "observed versus expected" cost differential was measured for each surgeon; this O/E cost ratio was then compared with PROs. Results: A total of 431 patients were included in the analysis. There were no differences in comorbidities, age, smoking status, or narcotic use. There was significant variation between surgeons in total 90-day costs, as well as variation between each surgeon's observed versus expected cost ratio. Despite these surgeon-specific cost variations, there were no differences in PROs across the participating surgeons. Conclusion: Intersurgeon cost variation in elective ACDF persists even after adjusting for patient comorbidities. There was no apparent correlation between increased surgeon-specific costs and 90-day PROs. These findings show there is opportunity for improvement in inter-surgeon cost variation without compromise in PROs. Level of Evidence: 3